2006
DOI: 10.1007/s11104-006-9108-1
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient fluxes via litterfall and leaf litter decomposition vary across a gradient of soil nutrient supply in a lowland tropical rain forest

Abstract: The extent to which plant communities are determined by resource availability is a central theme in ecosystem science, but patterns of small-scale variation in resource availability are poorly known. Studies of carbon (C) and nutrient cycling provide insights into factors limiting tree growth and forest productivity. To investigate rates of tropical forest litter production and decomposition in relation to nutrient availability and topography in the absence of confounding large-scale variation in climate and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 47 publications
5
95
0
5
Order By: Relevance
“…6d) compared to Crucitas, Campus, or Cascajoso as well as its achieved marginal annual deposition through leaf litter (Table 3) compared with Ca, K, Mg, and N suggest that this nutrient is available at very low levels in the soil solution or rather; it is easily retranslocated from leaf tissue to stems, branches, or other plant structures. Thus, further measurements are required to accurately estimate P nutrient resorption pools as has been previously pointed out (Duchesne et al 2001;Read and Lawrence 2003;Dent et al 2006). Conversely, the low levels of N deposition in Bosque Escuela compared with Crucitas, Campus, or Cascajoso could be associated with the capability of symbiotic nitrogen fixation potential of Fabaceae plant species observed at research sites (Zitzer et al 1996), since at Bosque Escuela, plant species belonging to the Fabaceae family represented only 4% of total species richness in the experimental plot, while in Crucitas, Campus, and Cascajoso, this taxonomic proportion reached values of about 20, 25, and 12%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6d) compared to Crucitas, Campus, or Cascajoso as well as its achieved marginal annual deposition through leaf litter (Table 3) compared with Ca, K, Mg, and N suggest that this nutrient is available at very low levels in the soil solution or rather; it is easily retranslocated from leaf tissue to stems, branches, or other plant structures. Thus, further measurements are required to accurately estimate P nutrient resorption pools as has been previously pointed out (Duchesne et al 2001;Read and Lawrence 2003;Dent et al 2006). Conversely, the low levels of N deposition in Bosque Escuela compared with Crucitas, Campus, or Cascajoso could be associated with the capability of symbiotic nitrogen fixation potential of Fabaceae plant species observed at research sites (Zitzer et al 1996), since at Bosque Escuela, plant species belonging to the Fabaceae family represented only 4% of total species richness in the experimental plot, while in Crucitas, Campus, and Cascajoso, this taxonomic proportion reached values of about 20, 25, and 12%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Dent et al (2006) have also suggested that the quantity and nutrient content of small litter decreased along a gradient of soil nutrient availability from alluvial forest (fertile soil) through sandstone forest (least fertile).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the miscellaneous fraction of litter production was correlated with rainfall in all habitats (R 2 >0.42) and that the peaks in that fraction occurred mainly at the beginning of the rainy season (in October, November and December). After the leaf fraction, fragments of branches and trunks are the largest contributor to total litterfall in an ecosystem (Martins & Rodrigues 1999, Dent et al 2006Cianciaruso et al 2006, Köhler et al 2008, Valenti et al 2008. During the dry season, twigs and branches can show xylem cavitation, which results in death from embolism (Tyree & Sperry 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, litter production is not spatially homogeneous within a given ecosystem. The presence of gaps (Martins & Rodrigues 1999), as well as variations in soil depth and fertility (Dent et al 2006, Jacobi et al, 2007, influence the pattern of vegetation cover, resulting in heterogeneous litterfall (Prescott 2002). Spatial and temporal variations in substrate water availability (Lawrence 2005), floristic composition (Costa et al 2004), successional stage (Martius et al 2004, Chave et al 2010 and photoperiod (Lei 1999), together with the mechanical action of rain and wind (Cianciaruso et al 2006;Terror et al 2011), affect the amount of deciduous components lost by plants, as well as the dynamics and structure of the community of decomposers in the soil, and, consequently, the productivity of the ecosystem (Prescott 2002;Martius et al 2004, Fisk et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…because optimal 15 decomposition rates are achieved only in a narrow saturation range (Bell et al, 2008; Ju et al, 2006; 16 Porporato et al, 2003;Van Gestel et al, 1992). Owing to the strong dependence of ecological processes on 17 soil moisture, linear and non-linear interactions and feedbacks exist between hydrological processes and soil 18 ecosystem functioning (Curiel Yuste et al, 2007;Misson et al, 2005;Scott-Denton et al, 2006; Van Gestel 19 et al, 1993) A second crucial external forcing factor for SOM and soil productivity -related to vegetation rather than to 5 climate -is the amount and quality of the litter input (Dent et al, 2006; Elliott et al, 1993; Manzoni et al, 6 2008;Paul et al, 2001;Sørensen, 1974). In particular, the C to N ratio (C/N) of the added litter is a very 7 sensitive parameter.…”
mentioning
confidence: 99%